Role of Topical Papaya Application in Debridement of Deep Burn Wounds - Sajid Rashid, Hasnain Khan, Yasir Iqbal (Journal of Rawalpindi Medical College, 2021)
Objective: To study the role of topical papaya application in managing deep burn wounds in terms of proteolytic enzymatic debridement for wound bed preparation. Material and Methods: This was a descriptive study carried out at Rawalian burn centre holy family hospital Pakistan from 12-10-2019 to 11-1-2020 over a period of 03 months. A total of 30 patients were included in the study (n=30). A convenient non-probability sampling technique was used for allocating patients to the study after getting written informed consent. For patients included in the study, papaya dressing was used for debridement and wound bed preparation of deep burn wounds. Results: There were 19 (63.3%) female and 11 (36.7%) male patients. The age range of patients was 10y to 50y with a mean of 28 years and SD ± 8.06 Patients included in the study had TBSA ranging from 10% to 35% with a mean of 19.8% and SD ± 6.82%. On average 7 dressings (Range 5-7) were required to achieve pink healthy granulation tissue. Out of total 30 patients (n=30) included in the study, good healing with the production of pink granulation was seen in 27 patients (81%) while in the rest of the 03 patients minor surgical debridement was required to achieve the pink granulation tissue bed for skin graft. Conclusion: Based on the results of this study it can be concluded that Papaya is an effective, safe, and rapid enzymatic proteolytic debriding agent of plant origin for deep burn wounds which promotes the growth of pink healthy granulation tissue with a minimal number of dressings. This granulation tissue readily accepts split-thickness skin graft.